Таинственный сапфир апостола Петра: [роман] / Наталья Александрова - Александрова Наталья Николаевна (Артефакт & Детектив, 2015)
Экземпляры: АБ (20150923) / Инвентарный номер: 59541 / Цена: 187.00 / Сис.шифр: Р2 / Авт.знак: А-46 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)